Talent Selection Strategies and Relationship With Success in European Basketball National Team Programs - Kalén, Anton; Padrón-Cabo, Alexis; Lundkvist, Erik; Rey, Ezequiel; Pérez-Ferreirós, Alexandra (Frontiers in Psychology, 2021)
There is limited knowledge of the talent selection strategies used by national sporting organizations to identify and develop talented players in basketball. Therefore, we aimed to explore differences in selection strategies between European youth basketball national team programs, and how they relate to the program’s success. Specifically, we examined differences in the number of youth national team players and within-country variance in the 1988-1999 generations between 38 countries (n men = 38, women = 32). Further, we tested if the number of youth national team players and within-country variance was related to the national teams senior ranking, youth ranking, and youth-to-senior player promotion, using generalized Bayesian multilevel models. We further checked the moderating effect of the sport’s popularity in each country. On average, 15.6 ± 2.0 male and 12.4 ± 1.8 female players were selected per generation. Over a third of the national teams consistently selected a higher or lower number of players than the average, with a difference of 8.1 players (95% CI [5.8, 10.8]) for men and 7.6 players (95% CI [5.4, 10.0]) for women between the countries with the highest and lowest average. When licensed players were used as moderator, the differences decreased but did not disappear, in both genders. There was an above 99.2% probability that a higher number of players was positively related to higher men’s senior and youth rankings, and women’s youth ranking. Within countries, generations with a higher number of youth players generated more senior players, with a probability of 98.4% on the men’s, and 97.3% on the women’s side. When licensed players were used as moderator, the probabilities for these relationships remained largely unaffected, apart from women’s youth ranking, which sank to 80.5%. In conclusion, the selection strategy in basketball national team programs varies between European countries and selecting a higher number of players possibly relates to better long-term performance and more players promoted to the senior national teams. These findings show that talent development programs should make conscious decisions about their selection strategies as it can affect their success.